Fungsi Naskah Akademik dalam Pembentukan Peraturan Perundang-undangan sebagai Cerminan Politik dan Hukum - Aisyah Oktavia Dewi; Tasya Amanda Mahdalena; Yuanita Ayu Virli; Nayla Zhei Aurel Meilan Permana; Ratna Christanti Sari Dewi (Fakultas Hukum, UPN Veteran Jawa Timur, 2026)
Academic Paper is a paper derived from the results of research or legal studies on a particular problem that can be scientifically accounted for regarding the regulation of the problem in a Draft Law, Draft Provincial Regulation, or Draft Regency/City Regulation which can be a solution to the problems and needs of the community regarding law in Legislation. In order to realize good regulations, a good academic paper is needed from community participation. With this in mind, this study will discuss the background of the need for an academic paper in the formation of legislation, in order to achieve legal ideals and for the realization of the principles of the formation of good legislation. The function of an academic paper is as a scientific paper that can be accounted for containing the background, the purpose of the preparation, the targets to be achieved so as to provide an overview of the agency, the scope of legislation, and provide a reflection for politics and law. Keywords: Academic Paper; Formation; Legislation.